The Role of Literary Elocutions In Independence Movement. An Analysis - Rabia Qudoos (بازیافت, 2022)
Oratory one of the oldest mode of communication has been source of preaching ideology, knowledge, civilization and culture.This research paper reveals the tradion, significance and role of Literary Elocutions from Mujadid,s literary tinged letters to Molana zafar Ali khan, Abul kalam azad and Hasrat mohani,s oratory journalism;and from Pandit Jawahar Lal Nehru,Waqar ul Mulk, Nawab Yar Jang Bahadur to Ali Brothers, Ahmad Saeed Dehlvi, Shabbir Ahmad Usmani and Allama Iqbal,s political Elocutions.The paper have encompasses the services of literary and oratory genius of the age.The key role of oration in the freedom movement can not be without these sermons it would not have accomplished it set goals.